Analisis Efektivitas Implementasi Sistem Reservasi Online Pasien Rawat Jalan Pada Poli Jantung Berbasis Web Di Rumah Sakit TK II Udayana - Anak Agung Istri Dwintya Putri; I Wayan Widi Karsana; Ni Made Diaris (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2022)
Background: The first point of contact for patients seeking medical attention at the hospital is patient registration. Of course, the hospital needs to be able to deliver quality care. Hospitals, particularly in Bali, have a system in place for online reservations. Patients who wish to receive treatment at the cardiac polyclinic must first wait in line in the morning in order to receive a queue number before being able to receive treatment in the afternoon because the Tk II Udayana Hospital's outpatient registration system does not currently use an online reservation system. This study's objective was to develop an online reservation system for outpatients at Tk II Udayana Hospital's web-based cardiac polyclinic. Methods: The study design used was the Pre Experimental Design method. Create an online registration system in the form of a web using the System Development Life Cycle or SDLC development stage. The samples used in this study were registration officers and patients using non-probability sampling technique with quota sampling. The instrument in this study used an observation checklist, stopwatch and also a questionnaire that was used, namely the usability USE questionnaire by Amond M Lund. Results: The study's usability test findings showed a percentage of 78.90%, which is considered